2018
DOI: 10.1111/dmcn.13668
|View full text |Cite
|
Sign up to set email alerts
|

Muscle tone assessments for children aged 0 to 12 years: a systematic review

Abstract: AIM The aim of this study was to identify and examine the psychometric properties of muscle tone assessments for children aged 0 to 12 years.METHOD Four electronic databases were searched to identify studies that included assessments of resting and/or active muscle tone. Methodological quality and overall psychometric evidence of studies were rated using the COnsensus-based Standards for the selection of health Measurement INstruments checklist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 50 publications
(83 reference statements)
1
20
0
Order By: Relevance
“…At the search stage, articles were included if they were published in English, potentially leading to assessment tools used exclusively in non‐English speaking countries being excluded from the review. During the data analysis stage, COSMIN was used to provide a review of study quality; however, it was originally designed for patient‐reported outcomes; therefore, minor modifications were described in the methods, which is consistent with a previous review 26 . Finally, the decision tree is a dynamic tool that should be revised when an updated systematic review is performed on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the search stage, articles were included if they were published in English, potentially leading to assessment tools used exclusively in non‐English speaking countries being excluded from the review. During the data analysis stage, COSMIN was used to provide a review of study quality; however, it was originally designed for patient‐reported outcomes; therefore, minor modifications were described in the methods, which is consistent with a previous review 26 . Finally, the decision tree is a dynamic tool that should be revised when an updated systematic review is performed on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Since COSMIN ratings were designed for patient‐reported outcomes (questionnaires), a modified sample size rating was used for this systematic review of clinical assessments. Sample size was reported as ‘excellent’ if either: (1) the study included a sample size calculation that demonstrated sufficient statistical power; 26 or (2) in the absence of this calculation, if the sample size met the COSMIN criteria 24,25 . Each study's quality is reported in Tables S1 to S3 (online supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…Goo, Johnston and Tucker [20] describe muscle tone as the individual's readiness to respond to gravity. The teacher that identified the learner with low muscle tone said it was quite obvious that something was amiss, because the learner would slump when seated, whether in a chair or on the carpet.…”
Section: Sub-theme: Low Muscle Tonementioning
confidence: 99%
“…In their systematic review, Goo et al. have bravely attempted to do just that, but have they achieved their objective? In fact, they have analysed the properties of the components of developmental scales that could only be very loosely associated with our ambiguous concept of tone. They claim, for example, that 21 components from the numerous developmental scales they reviewed were consistent with Sanger et al.…”
mentioning
confidence: 99%
“…Perhaps even more concerning was the poor intrarater reliability (assessors didn't agree with themselves on retesting) which suggests that either the status of the participants is very variable, the measurements intrinsically variable, or that the concept in the assessor's head changes. In any case, the components of the developmental scales reviewed by Goo et al . are likely to have limited value in charting neurological development and thus predicting developmental problems.…”
mentioning
confidence: 99%